Modelling the cost per ulcer treated of incorporating episodic treatment for HSV-2 into the syndromic algorithm for genital ulcer disease. Issue 3 (2nd April 2008) - Vickerman, P; Ndowa, F; Mayaud, P
Abstract : Background: The proportion of genital ulcer disease (GUD) due to herpes simplex virus type-2 (HSV-2) has increased in sub-Saharan Africa. The most recent 2003 WHO syndromic GUD algorithm includes antiviral treatment for HSV-2 for anyone with "typical" symptoms/signs, and suggests that all GUD patients receive treatment for HSV-2 in settings where HSV-2 GUD aetiology is greater than 30%. The previous algorithm (1994) only targeted Haemophilus ducreyi (HD) and Treponema pallidum (TP). Methods: A static deterministic model was used to compare the cost per ulcer treated of using the 1994 and 2003 algorithms amongst individuals presenting with GUD, with sensitivity analyses for different economic and epidemiological scenarios. Results: Except when the proportion of ulcers due to HD/TP (defined as ulcer prevalence) is high (>40%), and HSV-2 ulcer prevalence is low (<30%), the 2003 algorithm should result in more patients receiving the correct treatment (correct drugs for the syndrome) than the 1994 algorithm, and it will cost less per ulcer treated if HSV-2 treatment costs less than US$2. Greatest impact in terms of ulcers treated is achieved with the 2003 algorithm if HSV-2 treatment is given to all GUD patients. The incremental and/or relative cost per ulcer treated of doing this, compared to only treating those with typical symptoms/signs, is reduced if the HSV-2 ulcer prevalence is high and/or the HSV-2 treatment cost or sensitivity of HSV-2 ulcer diagnosis (using symptoms/signs) is low. Conclusions: In certain scenarios, including HSV-2 treatment can increase the number of ulcers treated and reduce the cost per ulcer treated of GUD syndromic management.